An Analytical Study to Stepping Transmission for a Hybrid Stepper Motor (Damascus University Journal for engineering sciences, 2024)
This research aims to explaining and physical analysis to stepping transmission for hybrid stepper motor, stepping transmission means the rotor position movement is step by step or dynamic single step response.The simplified mathematical model for two phase hybrid stepper motor was represented by using the computer program Matlab/Simulink, which describes their mechanical and electrical dynamic behavior of the mentioned motor was done. Whereas, the motor and drive system was modeled in order to run on one phase on mode.It have illustrated computing simulation results and physical analysis for current waves and we have explained varieties of electromechanical torque which is produced in the motor and its relationship with rotor position during the movement from position to other.
Keywords: Hybrid Stepping Motor; Modeling Step Motor; Mathematical Model of Step Motor; Dynamic Characteristics